Instructional Models for Enhancing Science Literacy Skills: A Literature Review - Irman Muliadi; Lalu Azikri Amrullah; Ahmad Hardyan Isnaini; Neli Yuliani; Salwa Salwa; Shelliana Iqlima (Indonesian Journal of Innovation and Educational Technology, 2026)
The low 2022 PISA scores highlight a serious challenge for scientific literacy in Indonesia, triggering the need for a transformation from conventional models toward pedagogical innovation. This study aims to analyze effective learning models for enhancing scientific literacy in the digital era. Using a Systematic Literature Review (SLR) method with the PRISMA model, this research reviewed 20 selected articles within the 2019–2026 interval. The analysis identified nine primary models and approaches proven to significantly improve scientific literacy: inquiry-based learning, problem-based learning (PBL), project-based learning (PjBL), STEAM-PjBL, guided inquiry, discovery learning, differentiated instruction, the ethnoscience approach, and the RADEC model. Findings indicate that these models, supported by technology integration such as interactive e-books and digital media, produce N-Gain scores in the medium to high categories. The ethnoscience approach also proved to enhance learning relevance through local wisdom. Despite their effectiveness, implementation still faces obstacles related to school facilities and teacher competency readiness. This study concludes that the synergy between student-centered innovative models and the reinforcement of teacher TPACK is crucial for creating meaningful, competitive, and adaptive science education for the modern era.